Systematic Literature Review: Pengaruh Green Accounting dan Good Corporate Governance terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Mediasi - Suci Mulyani; Sri Rahayu; Wirmie Eka Putra (Westscience Press, 2026)
This study aims to conduct a Systematic Literature Review (SLR) to analyze the influence of Green Accounting on company value and profitability, the influence of Good Corporate Governance (GCG) on these two variables, and the role of profitability as a mediator in the relationship. The SLR method was used to synthesize 20 relevant articles published between 2019 to 2025 with a focus on the theory of Legitimacy, Stakeholder, and Signaling. The results show that Green Accounting generally has a positive effect on company value through increased environmental transparency, although inconsistencies arise in the mining sector. GCGs consistently increase the value of companies through strong oversight mechanisms, but their effectiveness is reduced in companies with concentrated ownership. These variables also have a positive impact on profitability, with Green Accounting improving long-term operational efficiency and GCG reducing conflicts of interest, although upfront costs may weigh on performance temporarily. Profitability acts as a partial mediator, giving investors a positive signal and increasing valuations. Green Accounting and GCG practices contribute significantly to corporate sustainability, especially in Indonesia, but require stricter regulatory support. Research gaps include methodological variations and a lack of focus on specific sectors, so further research is needed for better generalizations.